Análise comparativa entre padrões de interpretação audiométrica: estudo de caso com trabalhadores de uma indústria geradora de energia elétrica - Cota, Jussara Maria Oliveira (2003)
In the last years, the scientific community has been making efforts in the sense to establishing technical criteria for standardization of the audio logical evaluation and the procedures of control to the noxious effects of the noise about the worker's health. On April 09, 1998 it was promulgated the Resolution 19 that proposes the parameters normalization for evaluation occupational audio logical. The present study is destined to verify in that measured the Resolution 19 contributed for the attendance of the evolution of the hearing loss along the years, through the application of the Resolution 19 in a case study accomplished with workers in a electric power generating industry. 1540 audiometry exams of 147 workers group were analyzed, with age between 29 and 56 years. The data were obtained by consultation to the handbooks, considering as cut line the period between 1982 and 2002. The audiometric were classified according to the methods Davis & Silverman, Merluzzi, Pereira, Costa and Resolution 19. The prevalence of hearing losses for high levels of resonant pressure (PAINPSE), in the analysis of only audiometry exams, was similar among the appraised methods, except in the method Davis & Silverman, whose frequency strip doesn't contemplate this loss type. The analysis of exam sequential audiometric, done by the Resolution 19, it presented prevalence of 6,8% workers with occurrence of PAINPSE and 3,4% workers with aggravation of the loss. The results suggest that the Resolution 19 was the method that best allowed the equalization of the results, whose standardization criteria facilitated the individual attendance of the workers' audition along the years, according to criteria of the Resolution 19